56 57 and 58 are the three numbers that work
If the bases ar same, assume exponents are same
if
x^z=x^m
assume z=m
so
base is both 7 therefor
3x+5=1-x
solve
add x
4x+5=1
minus 5
4x=-4
divide 4
x=-1
Step-by-step explanation:
by comparing both f (x) and g (x)
we get
3x-1=2x-1/x
by this way we can get the value of X and put the value of X in f (x) and g (x)
![\sf \frac{6}{30} = \frac{x}{100}](https://tex.z-dn.net/?f=%20%5Csf%20%5Cfrac%7B6%7D%7B30%7D%20%20%3D%20%20%5Cfrac%7Bx%7D%7B100%7D%20)
Solve for x by cross multiplication
![\sf6 \times 100 = x \times 30](https://tex.z-dn.net/?f=%20%5Csf6%20%5Ctimes%20100%20%3D%20x%20%5Ctimes%2030)
![\sf \: 600 = 30x](https://tex.z-dn.net/?f=%20%5Csf%20%5C%3A%20600%20%3D%2030x)
- Swap the sides of equation
![\sf \: 30x = 600](https://tex.z-dn.net/?f=%20%5Csf%20%5C%3A%2030x%20%3D%20600)
- Divide both sides of equation by 30
![\boxed{ \tt \: x = 20}](https://tex.z-dn.net/?f=%20%5Cboxed%7B%20%5Ctt%20%5C%3A%20x%20%3D%2020%7D)
The surface area of the square pyramid is: 451 cm²
The lateral surface area of the square pyramid = 330 cm²
<h3>What is the Lateral Surface Area and Surface Area of a Square Pyramid?</h3>
Surface area = a² + 2al, where a is the base edge and l is the slant height.
Lateral Surface Area = 2al.
Given the following:
Surface area = a² + 2al = 11² + 2(11)(15)
Surface area = 451 cm²
Lateral Surface Area = 2al = 2(11)(15)
Lateral Surface Area = 330 cm²
Learn more about square pyramid on:
brainly.com/question/3688277